3D Printing Technology for Water Treatment Applications - Pandey, Jitendra Kumar; Manna, Suvendu; Patel, Ravi Kumar (Additive manufacturing materials and technologies, 2023)
3D Printing Technology for Water Treatment Applications provides a state-of-the-art presentation on the application of 3D printing technology in water treatment. The book discusses numerous processes and their scope for improvement through the use of 3D-printing technology, including pollutant separation from water and an overview of the advantages and disadvantages of different 3D printed technology over current technologies. In addition, the future outlook for device development using 3D printing water purification is explored. Finally, sustainability issues relating to 3D printing-based water purification processes are discussed, describing specific technologies such as 3D printed membranes. This book will serve as a vital resource for scientists, engineers and environmental professionals working in water treatment technologies.